BIN1 rs744373 SNP and APOE alleles specifically associate to common diseases - Cachide, Maria; Carvalho, Liliana; Rosa, Ilka Martins; Wiltfang, Jens; Henriques, Ana Gabriela; da Cruz e Silva, Odete A. B. (Frontiers in Dementia, 2022)
APOE E4 and BIN1 are the two main genetic risk factors for sporadic Alzheimer's Disease (AD). The BIN1 rs744373 variant is more frequently associated with AD risk. This study addressed the association of APOE and rs744373 to specific characteristics in a Portuguese primary care-based study group, denoted pcb-Cohort. The study included 590 participants from five primary care health centres in the Aveiro district of Portugal. Individuals were evaluated and scored for cognitive and clinical characteristics, and blood samples were collected from the volunteers meeting the inclusion and exclusion criteria (N = 505). APOE and BIN1 genotypes were determined and associated with cognitive characteristics and the presence of other diseases that might contribute to cognitive deficits, namely diabetes, dyslipidemia, and cardiovascular and respiratory diseases. The results show that APOE E4 carriers significantly associated with poorer cognitive performance (OR=2.527; p=0.031). Additionally, there was a significant risk of dyslipidemia for APOE 4 carriers (OR=1.804 ; p=0.036), whereas BIN1 rs744373 risk-allele carriers were at a significantly lower risk of having dyslipidemia (OR=0.558 ; p=0.006). Correlations were evident for respiratory diseases in which APOE 4 showed a protective tendency (OR=0.515 ; p=0.088), and BIN1 had a significative protective profile (OR=0.556 ; p=0.026). Not of statistical significance, APOE E2 showed a trend to protect against diabetes (OR=0.342 ; p=0.093), in contrast BIN1 rs744373 risk-allele carriers were more likely to exhibit the disease (OR=1.491 ; p=0.099). The data here presented show that the two top genetic risk factors for sporadic AD impact a similar group of pathologies.